Mucosal Administration of E-selectin Limits Disability in Models of Multiple Sclerosis - Quandt, Jacqueline A.; Becquart, Pierre; Kamma, Emily; Hallenbeck, John (Frontiers in Molecular Neuroscience, 2019)
E-selectin plays an important role in mediating rolling of leukocytes along and thus subsequent extravasation across activated endothelial cells comprising the microvasculature of the blood brain barrier (BBB). In multiple sclerosis (MS) and other inflammatory disorders of the central nervous system (CNS), the microvasculature is altered and immune cells infiltrate the brain and spinal cord contributing to damage, demyelination and ultimately disability. While mucosal administration is typically used to effect lymphocyte hyporesponsiveness or tolerance to suspect autoantigens, intranasal administration to E-selectin has previously been shown to protect against CNS inflammatory insults. We characterized the potential for mucosal administration of E-selectin to modulate CNS autoimmunity in the experimental autoimmune encephalomyelitis (EAE) model of MS. Intranasally administered E-selectin reduced swelling by as much as 50% in delayed-type hypersensitivity reactions compared to ovalbumin-tolerized controls. Intranasal E-selectin delivery prior to disease induction with myelin oligodendrocyte glycoprotein (MOG)35-55 reduced disease severity and total disease burden by more than 50% compared to PBS-tolerized animals; this protection was not associated with differences in the magnitude of the autoimmune response. Examination after the onset of disease showed that protection was associated with significant reductions in inflammatory infiltrates throughout the spinal cord. Tolerization to E-selectin did not influence encephalitogenic characteristics of autoreactive T cells such as IFN-gamma or IL-17 production. Clinical disease was also significantly reduced when E-selectin was first delivered after the onset of clinical symptoms. Splenic and lymph node populations from E-selectin-tolerized animals showed E-selectin-specific T cell responses and production of the immunomodulatory cytokine IL-10. Transfer of enriched CD4+ T cells from E-selectin tolerized mice limited disability in the passive SJL model of relapsing remitting MS. These results suggest a role for influencing E-selectin specific responses to limit neuroinflammation that warrants further characterization for the potential to mitigate neurodegeneration in disorders such as MS.